Enhancing Indonesian Language Learning Through TBLT and Google Classroom in Higher Education: Students’ Perceptions - Nita, Olin (JOLLT Journal of Languages and Language Teaching, 2025)
Many studies have investigated Task-Based Language Teaching(TBLT) in language learning, but studies on the implementation of TBLT assisted by Digital Media in the current era have been rarely conducted by scholars. This study is intended to investigate students’ perception of the implementation of TBLT assisted by Google Classroom, focusing on their learning experiences, the challenges they face, and the benefits and effectiveness of TBLT. This explanatory sequential mixed method involved 60 students of theÂ Civil Engineering and Mechanical Engineering Study Programs at Eka Sakti University, Padang. The data of this study were gathered using a questionnaire and semi-structured interview. The quantitative data were analyzed quantitatively using descriptive statistics, while qualitative data were analyzed qualitatively using an interactive model. The results show that studentsâ€™ perception of learning experiences, benefits, and effectiveness aspects were positive, while some students faced some challenges (e.g., task instruction, time allocation to do the tasks, internet connection, and work independently) in the challenge aspect in Indonesian language learning using TBLT assisted by Google Classroom. Although they faced some challenges, they overcame them by collaborating with their classmates in conducting institutions from theÂ lecturer. Thus, it can be concluded that TBLT assisted by Google Classroom is effective in enhancing studentsâ€™ Indonesian language skills and components, participation, learning interest, collaboration, and engagement. Thus, the TBLT approach integrated with Google Classroom is suggested to be employed by language instructors in teaching the Indonesian language course in Higher Education for non-Indonesian major students.